Unfolding the physics of URu2Si2 through silicon to phosphorus substitution - A. Gallagher (Nature Portfolio, 2016)
The heavy fermion compound URu2Si2displays a hidden order phase and superconductivity at low temperatures. Here, the authors perform substitution studies—partially replacing silicon with phosphorus—and study the effects on hidden order and superconductivity.